Узагальнення органами КДБ УРСР досвіду боротьби з підпіллям ОУН та УПА: до створення відомчої тематичної колекції архівних документів (1959–1964 рр.) - Іщук, О. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2009)
The author investigated the process of creation of subject collection of archival documents of Branch State Archive of Security Service of Ukraine about the struggle of State Security of the USSR against OUN–UPA. The prospectuses of textbooks for staff of KGB of the USSR were published.